PENGEMBANGAN KETERAMPILAN BERFIKIR KRITIS PADA REMAJA MELALUI PENERAPAN METODE DEBAT - Syahdeli, Muhamad Ilham; Budiman, Rido; Rikmasari, Rima (An-Nizam, 2023)
In a research journal focusing on community service programs aimed at developing critical thinking skills through debate methods in high schools, the research results indicate that this program has significantly enhanced the critical thinking abilities, speaking skills, and argumentation skills of male and female students. The program has provided valuable experiences in research, teamwork, and a deeper understanding of complex issues. Participants in the program have also reported improvements in their ability to communicate clearly and assertively, boosting their confidence in expressing their opinions and effectively responding to questions and counterarguments.Throughout the debate process, students have had the opportunity to delve into specific topics, aiding them in better comprehending complex issues. This, in turn, contributes to more critical assessments and better decision-making across various aspects of life.Expanding the implementation of this program to various high schools is expected to assist more students in developing crucial critical thinking skills vital for both education and daily life. Continuous monitoring and evaluation are essential to continually enhance the program's effectiveness. Additionally, providing more supportive resources, such as books, access to literature, and in-depth training for educators, is necessary to elevate the program's quality.Consequently, this community service program has brought about significant positive impacts by enhancing the critical thinking skills, speaking abilities, and argumentation skills of high school students, preparing them to face future challenges.